2011
DOI: 10.1038/ijir.2011.33
|View full text |Cite
|
Sign up to set email alerts
|

The effect of simvastatin in penile erection: a randomized, double-blind, placebo-controlled clinical trial (Simvastatin treatment for erectile dysfunction—STED TRIAL)

Abstract: The aim of the study is to evaluate the effect of simvastatin in erectile dysfunction (ED) secondary to endothelial dysfunction. This study is a double-blind, randomized, placebo-controlled, clinical trial in patients with ED and endothelial dysfunction. Patients were randomized to receive 20 mg simvastatin (n ¼ 21) or placebo (n ¼ 20) daily for 6 months and subsequently 10 mg of vardenafil on demand for 4 weeks. Serum cholesterol, hormone profile, ultrasensitive C-reactive protein, the International Index of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…The primary findings of five studies was an improvement of erectile function after statins administration,1718192021 whereas, the other two studies had no significant difference between the statins and the control groups 2223. The methods used to assess erectile function was IIEF-5 in five trials,1718192223 and ED domain score in two trials 2021. The ED domain score could not be integrated in the meta-analysis because one study did not provide the standard deviation 20.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary findings of five studies was an improvement of erectile function after statins administration,1718192021 whereas, the other two studies had no significant difference between the statins and the control groups 2223. The methods used to assess erectile function was IIEF-5 in five trials,1718192223 and ED domain score in two trials 2021. The ED domain score could not be integrated in the meta-analysis because one study did not provide the standard deviation 20.…”
Section: Resultsmentioning
confidence: 99%
“…The ED domain score could not be integrated in the meta-analysis because one study did not provide the standard deviation 20. Hence, only the five studies applying IIEF-5 scores to evaluate erectile function were included in the meta-analysis 1718192223. We did not perform a test for funnel plot asymmetry because only five studies were included in the meta-analysis 1718192223.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the aforementioned studies, a double-blind, randomized, placebocontrolled, clinical trial in patients with ED and endothelial dysfunction reported no signifi cant difference in penile erection between those treated with simvastatin and the placebo group [ 39 ].…”
Section: Clinical Studiesmentioning
confidence: 97%
“…Overall, statin therapy alone [39], as well as in combination with PDE-5 inhibitor therapy, was shown to improve the sexual health related quality of life in ED patients but may not be considered an erectogenic drug [40]. Nevertheless, it is suspected that statin therapy may improve the effi cacy of PDE-5 inhibitor therapy in patients with endothelial dysfunction [40].…”
Section: Medical Treatmentmentioning
confidence: 99%